Caracterización del residuo pétreo de la industria minera del oro para la producción de hormigón en Uruguay - Tomeo Suárez, Fernando Daniel (2012)
In last century, both in Uruguay and in the world, there became evident the consolidation of the utilization of the reinforced concrete, as fundamental material, for the construction of structures of use in architecture and civil engineering works. This reality demanded the investigation in the materials area, as this way also of models of structural design. On the other hand, in the last decade, this process coincide with the strengthening of the gold’s mining industry in the North- East of the territory of Uruguay, extractive activity, generating of stony residues with big quantities and with important questions as for his environmental aggression. This work took as an aim the study of the technical viability of the use of this stony residue in the production of concrete, in substitution of the conventional coarse aggregate. The investigation included the characterization of the same one and the comparison with the aggregates of traditional use, as much as in what involves to the performance as regarding the quantification of generation and use. In the first part, there was analyzed the importance of the use of residues in the industry of the construction linked to the development of a politics that attends to the environmental problematic and there was relieved the destination of the residues, product of the mining industry, in countries of Latin America and the rest of the world that possess a significant experience in this productive activity. Later the contemporary analysis was included in the study on the coarse aggregates, vision that considers the active participation of the same ones in the fundamental properties of the concrete, investigating the particularities of the stony ones depending on his physical characteristics and his chemical composition. In the end, an experimental stage was developed working on the stony chosen residue, the product of a metamorphism of high degree in a mafica rock, and the obtained values were compared with those of the stony ones of common use in the industry of the construction in Uruguay and in several regions. The analysis of the results allows concluding that this stony residue has sufficient conditions from the technical point of view to be considered in the production of concrete, as a possible substitute for conventional coarse aggregate.